EFISIENSI PRODUKSI USAHATANI SAYURAN (CABAI, SAWI DAN KUBIS) DI KOTA PAGAR ALAM PROVINSI SUMATERA SELATAN - Lestari, Olpa Fuji; Hasyim, Ali Ibrahim; Situmorang, Suriaty (Lampung University, 2020)
This research aims to analyze the factors that affect production of vegetable (chili,mustard and cabbage)farming and the technical efficiency. The research was conducted in North Dempo and South Pagar Alam Subdistrict of Pagar Alam. Farmer respondents were chosen by using simple random sampling. Data were collected in May–Juny 2018 and analyzed using Cobb-Douglas production functionnamely frontier production function. The results showed that factors affecting the production of chili farming are area lands, seeds and nitrogen fertilizer. Factors affecting the production of mustard farming are landsize, seeds and potassium fertilizer, and pesticide. Factors affecting the production of cabbage farming are area landslandsizeand manure. Vegetable farming (chili, mustard and cabbage) is on an increasing return to scale (Ep>1) or in irrational area so that it does not meet the requirement for economic efficiency. Chili and mustard farming are technically efficient with an efficiency level greater than 70,00%. The level of technical efficiency of chili farming is 86,99% and mustard farming is 80,08%. Cabbage farming is not technically efficient because the efficiency level is below 70,00%, that is 68,72%.Key words: efficiency, farming, vegetable